Yona of the dawn. 27 - Kusanagi, Mizuho, 1979-; MacFarlane, Ysabet Reinhardt (Shojo beat manga., 2020)
"Princess Yona lives an ideal life as the only princess of her kingdom. Doted on by her father, the king, and protected by her faithful guard Hak, she cherishes the time spent with the man she loves, Su-won. But everything changes on her 16th birthday when tragedy strikes her family! ... Hak has confessed his feelings to Yona, but how will Yona react in response? Later, Zeno suggests heading to Kuuto and getting closer to Hiryuu Palace so that the Four Dragons can heal their wounds. But what will they do when a Kai Empire army attacks the Fire Tribe?"--